A novel integration of Web 3.0 with hybrid chaotic-hippo-optimized Blockchain framework for healthcare 4.0 - S Punitha; Preetha K S (Results in Engineering)
HealthCare 4.0 stands as a cutting-edge technology that integrates human-sourced data with communication systems to enable highly accurate clinical diagnostics and treatments. While sensor-based devices have simplified many aspects of daily life, these advancements also face significant security challenges, particularly in safeguarding patient information. In response, this research introduces a novel blockchain-based hybrid chaotic encryption and authentication for maintaining EHR transmissions aimed at robust and secure authentication within HealthCare 4.0. The complete framework incorporates the Infura Web API, using Python 3.19. To strengthen authentication security, modified Hippopotamus-evoked scroll maps are used to generate dynamic hashes in the genesis block formation, securing all EHR data in the proposed architecture. This entire framework was evaluated on the Ethereum Blockchain, leveraging Web 3.0, with Python 3.19 serving as the core programming environment for interface development. Security analysis was performed utilizing Burrows-Abadi-Needham (BAN) logic, while the framework's resilience was rigorously tested against NIST standards. Comparative testing highlights the model's superior defense capabilities against various attacks, surpassing other frameworks in complexity and robustness. The findings ultimately provide a comprehensive view of the optimized encryption scheme on blockchain technology and the future pathways for secure authentication frameworks in HealthCare 4.0.